DNA-PK inhibition synergizes with oncolytic virus M1 by inhibiting antiviral response and potentiating DNA damage. Issue 1 (December 2018) - Xiao, Xiao; Liang, Jiankai; Huang, Chunlong; Li, Kai; Xing, Fan; Zhu, Wenbo; Lin, Ziqing; Xu, Wencang; Wu, Guangen; Zhang, Jifu; Lin, Xi; Tan, Yaqian; et al.
Abstract Oncolytic virotherapy is a promising therapeutic strategy that uses replication-competent viruses to selectively destroy malignancies. However, the therapeutic effect of certain oncolytic viruses (OVs) varies among cancer patients. Thus, it is necessary to overcome resistance to OVs through rationally designed combination strategies. Here, through an anticancer drug screening, we show that DNA-dependent protein kinase (DNA-PK) inhibition sensitizes cancer cells to OV M1 and improves therapeutic effects in refractory cancer models in vivo and in patient tumour samples. Infection of M1 virus triggers the transcription of interferons (IFNs) and the activation of the antiviral response, which can be abolished by pretreatment of DNA-PK inhibitor (DNA-PKI), resulting in selectively enhanced replication of OV M1 within malignancies. Furthermore, DNA-PK inhibition promotes the DNA damage response induced by M1 virus, leading to increased tumour cell apoptosis. Together, our study identifies the combination of DNA-PKI and OV M1 as a potential treatment for cancers. Oncolytic virotherapy is a promising strategy for cancer treatment. In this study, the authors demonstrate that DNA-dependent protein kinase (DNA-PK) inhibition sensitizes cancer cells to M1 virus and improves therapeutic effects in refractory cancer models in vivo and in patient tumour samples.